Implementation of the “Babonisasi” system of environmentally friendly kampong chicken based on household waste for increasing income of KWT Banyusidi Village - Setyo Utomo; Nur Rasminati; Ajat Sudrajat (Universitas Muhammadiyah Magelang, 2023)
The purpose of this activity is to apply the